The Gita - The Song of Eternal Wisdom - Anant Pai; Amar Chitra Katha Pvt Ltd (Mumbai Amar Chitra Katha, 1977)
Gita, short for Bhagavad Gita, 'the Divine Song', is a philosophical dialogue in verse, in the Mahabharata. The setting is the start of the great war between cousins, Kauravas and Pandavas, when the forces on both sides come face-to-face on the battlefiel
Keywords: Amar Chitra Katha -- Amar Chitra Katha